Hubungan Antara Keterampilan Metakognisi dan Motivasi Belajar dengan Hasil Belajar IPA Siswa Kelas VIII SMP Negeri di Kecamatan Ujung Pandang Kota Makassar - Asmawati Asmawati; Firdaus Daud; Muhammad Danial (UNM Journal of Biological Education, 2022)
This study aims to (i) analyze how metacognitive skills are; (ii) analyze how learning motivation is; (iii) analyze how science learning outcomes (iv) analyze the relationship between metacognitive skills and science learning outcomes; (v) analyze the relationship between learning motivation and science learning outcomes; (vi) analyze the relationship between metacognitive skills and learning motivation with learning outcomes together with science learning outcomes for class VIII SMP Negeri Makassar City students. This research is an ex-post facto research. The population in the study was all students of class VIII of SMP Negeri in Ujung Pandang sub-district, Makassar City in the 2021-2022 academic year with a total of 717 students. The research sample was 345 students using cluster random sampling. Data collection techniques are questionnaires and documentation. Data were analyzed by descriptive and inferential statistical techniques. The results showed that (i) students' metacognition skills were classified as moderate, (ii) students' learning motivation was classified as moderate (iii) students' science learning outcomes were in the medium category, (iv) there was a relationship between metacognitive skills and science learning outcomes, (v) there were there is a relationship between learning motivation and learning outcomes in Biology, (vi) there is a relationship between metacognitive skills and learning motivation with science learning outcomes for eighth grade students of SMP Negeri in Ujung Pandang District, Makassar City.